Advanced Funk Studies: creative patern for the advanced drummer in the styles of today's funk drummers - LATHAM, Rick (1980)
berisi tentang: Explanaton of notation, Introductory exercises, Hi-hat openings, Combination exercises, Fill Patterns, Funk Pattern, Transcriptions, Solos